An alternative to MINFLUX that enables nanometer resolution in a confocal microscope - Masullo, Luciano Andrés (2022)
Localization of single fluorescent emitters is key for physicochemical and biophysical measurements at the nanoscale and beyond ensemble averaging. Examples include single-molecule tracking and super-resolution imaging by single-molecule localization microscopy. Among the numerous localization methods available, MINFLUX outstands for achieving a ~10-fold improvement in resolution over wide-field camera-based approaches, reaching the molecular scale at moderate photon counts. Widespread application of MINFLUX and related methods has been hindered by the technical complexity of the setups. Here, we present RASTMIN, a single-molecule localization method based on raster scanning a light pattern comprising a minimum of intensity. RASTMIN delivers ~1–2 nm localization precision with usual fluorophores and is easily implementable on a standard confocal microscope with few modifications. We demonstrate the performance of RASTMIN in localization of single molecules and super-resolution imaging of DNA origami structures.